2023
DOI: 10.1128/spectrum.02687-22
|View full text |Cite
|
Sign up to set email alerts
|

A Beta Strain-Based Spike Glycoprotein Vaccine Candidate Induces Broad Neutralization and Protection against SARS-CoV-2 Variants of Concern

Abstract: Continuous emergence of adaptive mutations of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to challenge the use and development of existing vaccines and drugs. The value of variant-based vaccines that are capable of inducing a higher and broader protection immune response against SARS-CoV-2 variants is currently being evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Newly developed SARS-CoV-2 vaccines can take consensus sites of majority variants ( 23 ) or use conserved S2 subunit of the spike protein ( 24 ). Alternatively, the potency of existing vaccines with the original strain antigens can be increased by adjuvant, resulting in a robust immune response that can effectively neutralize even variants that evade the immune system ( 23 , 25 28 ). Numerous studies have indicated that toll-like receptor (TLR) agonists are effective as mucosal adjuvants ( 29 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Newly developed SARS-CoV-2 vaccines can take consensus sites of majority variants ( 23 ) or use conserved S2 subunit of the spike protein ( 24 ). Alternatively, the potency of existing vaccines with the original strain antigens can be increased by adjuvant, resulting in a robust immune response that can effectively neutralize even variants that evade the immune system ( 23 , 25 28 ). Numerous studies have indicated that toll-like receptor (TLR) agonists are effective as mucosal adjuvants ( 29 31 ).…”
Section: Introductionmentioning
confidence: 99%